Performance and Characterization of Seebeck Coefficient and Power Factor in CMC/Glycerin Gel Electrolyte Based Ionic Thermoelectric - Robiandi, Fadli; Shoodiqin , Dian Mart; Mayantasari, Menasita (Department of Physics Education, Universitas Mataram, 2024)
Ionic thermoelectric (i-TE) materials have gained significant attention for their potential to convert low-temperature thermal energy into electrical energy. In this study, gel electrolyte-based i-TE materials have been synthesized using carboxymethyl cellulose (CMC), glycerin and H3PO4 solution as electrolyte. Analysis of thermoelectric properties such as Seebeck coefficient and power factor of the gel electrolyte has been carried out. In this study, ionic conductivity and potential difference or output voltage of CMC/glycerin gel electrolyte were measured. The results of this study indicate that the ionic conductivity and output voltage of the CMC/glycerin sample increase with temperature, whereas the Seebeck coefficient and power factor tend to decrease as the temperature gradient between the hot and cold parts of the CMC/glycerin gel electrolyte sample increases. These findings suggest that the CMC/glycerin-based polymer gel electrolyte has potential for use in i-TE devices, particularly in applications where high power output is required.